Development and pilot of clinical performance indicators for English ambulance services. Issue 4 (12th April 2010) - Siriwardena, A Niroshan; Shaw, Deborah; Donohoe, Rachael; Black, Sarah; Stephenson, John
Abstract : Introduction: There is a compelling need to develop clinical performance indicators for ambulance services in order to move from indicators based primarily on response times and in light of the changing clinical demands on services. We report on progress on the national pilot of clinical performance indicators for English ambulance services. Method: Clinical performance indicators were developed in five clinical areas: acute myocardial infarction, cardiac arrest, stroke (including transient ischaemic attack), asthma and hypoglycaemia. These were determined on the basis of common acute conditions presenting to ambulance services and in line with a previously published framework. Indicators were piloted by ambulance services in England and results were presented in tables and graphically using funnel (statistical process control) plots. Results: Progress for developing, agreeing and piloting of indicators has been rapid, from initial agreement in May 2007 to completion of the pilot phase by the end of March 2008. The results of benchmarking of indicators are shown. The pilot has informed services in deciding the focus of their improvement programme in 2008–2009 and indicators have been adopted for national performance assessment of standards of prehospital care. Conclusion: The pilot will provide the basis for further development of clinical indicators, benchmarking of performance and implementation of specific evidence-based interventions to improve care in areas identified for improvement. A national performance improvement registry will enable evaluation and sharing of effective improvement methods as well as increasing stakeholder and public access to information on the quality of care provided by ambulance services.